2020
DOI: 10.1186/s12870-020-2319-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shell sand burial on seedling emergence, growth and stoichiometry of Periploca sepium Bunge

Abstract: Background: Sand burial plays an irreplaceable and unique role in the growth and distribution of vegetation on the Shell Dike Island in the Yellow River Delta. There are still some unknown on the effects of sand burial on the morphology, biomass, and especially the stoichiometry of Periploca sepium, as well as the relationship between these factors. Results: Shell sand burial depth had a significant influence on seedling emergence, growth, and biomass of P. sepium. Shallow sand burial shortened the emergence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Therefore, sand burial is an important stress factor that restricts the growth, survival, and distribution of sand dune plants [4,22]. Previous studies have revealed that sand burial can have both positive and negative effects on seed germination and seedling emergence in desert steppe ecosystems [8,23]. In this study, with the increase in sand burial depth, seed germination percentage, germination energy, and germination index exhibited a decreasing trend, and the top 10 combined treatments all excluded sand burial, indicating that sand burial was the most critical factor inhibiting the germination of S. alopecuroides seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sand burial is an important stress factor that restricts the growth, survival, and distribution of sand dune plants [4,22]. Previous studies have revealed that sand burial can have both positive and negative effects on seed germination and seedling emergence in desert steppe ecosystems [8,23]. In this study, with the increase in sand burial depth, seed germination percentage, germination energy, and germination index exhibited a decreasing trend, and the top 10 combined treatments all excluded sand burial, indicating that sand burial was the most critical factor inhibiting the germination of S. alopecuroides seeds.…”
Section: Discussionmentioning
confidence: 99%